Human subject testing of leakage in a loose-fitting PAPR. - Johnson AT; Koh FC; Jamshidi S; Rehak TE (Journal of Occupational & Environmental Hygiene, 2008)
Leakage from loose-fitting PAPRs (powered air-purifying respirators) can compromise the safety of wearers. The Martindale Centurion MAX multifunction PAPR is a loose-fitting PAPR that also incorporates head, eye, and ear protection. This respirator is used in mines where coal dust usually is controlled by ventilation systems. Should the respirator be depended on for significant respiratory protection? Ten human volunteers were asked to wear the Centurion MAX inside a fog-filled chamber. Their inhalation flow rates were measured with small pitot-tube flowmeters held inside their mouths. They were video imaged while they breathed deeply, and the points at which the fog reached their mouths were determined. Results showed that an average of 1.1 L could be inhaled before contaminated air reached the mouth. As long as the blower purges contamination from inside the face piece during exhalation, the 1.1 L acts as a buffer against contaminants leaked due to overbreathing of blower flow rate.